Influence of the flow structure on heat transfer in the condensation process of environmentally friendly refrigerants in mini-channels - Sikora, Małgorzata; Bohdal, Tadeusz (Instal, 2022)
During the condensation process in the mini-channels, the heat and mass transfer mechanisms change, resulting from the change in the vapor quality x and the void fraction φ, which in turn affect the process of formation of various flow structures. The measure of the energy efficiency of the process is the heat transfer coefficient α, which depends on the kind of the two-phase flow. This article presents the influence of the two-phase flow structures formed during the condensation process in horizontal pipe mini-channels on the heat transfer process. The research was carried out on three pro-ecological low-pressure refrigerants with low ODP and GWP coefficients, HFE7000, HFE7100, and Novec649. The condensation process took place in pipe mini-channels with an internal diameter of dh = 2.0; 1.2; 0.8; 0.5 mm
Keywords: condensation; mini-channels; flow structures; heat transfer; HFE7000; HFE7100; Novec649